Limiting the rise in core temperature during a rugby sevens warm-up with an ice vest - Taylor, L.; Stevens, C. J.; Thornton, H. R.; Poulos, N.; Chrismas, B. C. R. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To determine how a cooling vest worn during a warm-up could influence selected performance (countermovement jump [CMJ]), physical (global positioning system [GPS] metrics), and psychophysiological (body temperature and perceptual) variables. Methods: In a randomized, crossover design, 12 elite male World Rugby Sevens Series athletes completed an outdoor (wet bulb globe temperature 23-27°C) match-specific externally valid 30-min warm-up wearing a phase-change cooling vest (VEST) and without (CONTROL), on separate occasions 7 d apart. CMJ was assessed before and after the warm-up, with GPS indices and heart rate monitored during the warm-ups, while core temperature (Tc; ingestible telemetric pill; n = 6) was recorded throughout the experimental period. Measures of thermal sensation (TS) and thermal comfort (TC) was obtained pre-warm-up and post-warm-up, with rating of perceived exertion (RPE) taken post-warm-ups. Results: Athletes in VEST had a lower Tc (mean [SD]: VEST = 1.3°C [0.1°C]; CONTROL = 2.0°C [0.2°C]) from pre-warm-up to post-warm-up (effect size; ±90% confidence limit: -1.54; ±0.62) and Tc peak (mean [SD]: VEST = 37.8°C [0.3°C]; CONTROL = 38.5°C [0.3°C]) at the end of the warm-up (-1.59; ±0.64) compared with CONTROL. Athletes in VEST demonstrated a decrease in TS (-1.59; ±0.72) and TC (-1.63; ±0.73) pre-warm-up to post-warm-up, with a lower RPE post-warm-up (-1.01; ±0.46) than CONTROL. Changes in CMJ and GPS indices were trivial between conditions (effect size < 0.2). Conclusions: Wearing the vest prior to and during a warm-up can elicit favorable alterations in physiological (Tc) and perceptual (TS, TC, and RPE) warm-up responses, without compromising the utilized warm-up characteristics or physical-performance measures.